Identifying the factors for reducing turnover rate in aviation business: Bangladesh context - Nahar, Rezbin; Islam, Rafikul; Ullah, Kazi Tareq (Australian Academy of Business Leadership, 2017)
Managing employee turnover for any organization is considered one of the demanding tasks for today’s competitive business word. This has been evident as an enduring problem in the aviation business of Bangladesh. In recent days, the impact of employee turnover has received considerable attention of human resources professionals and senior management working in the sector. In Bangladesh, skilled employees join the aviation companies with high expectations, but reality frustrates them and forces to switch. As a result, gradually this sector is facing shortage of talents and failing to achieve their goals. Thus, this research aims to find out the influencing factors that help to reduce employee turnover in aviation industry. A survey questionnaire was administered among the employees of aviation companies targeting the purpose using random sampling method. Data collected are analyzed through descriptive statistics. Subsequently, multiple regression models are used to portray the causal relationship among variables. The paper provides necessary recommendations that will help reduce employee turnover and aid in retaining the qualified employees. The outcome will provide a new initiative to the human resources professionals and senior management of the sector to deal with the shortage of talents more efficiently.